Thought Stopping untuk Menurunkan Kecemasan Mahasiswa yang Sedang Menyusun Skripsi - Desi Wahyuni Sari; Sri Muliati Abdullah (Universitas Islam Indonesia, 2021)
Students who are writing a thesis often experience anxiety and need treatment so that their emotions are more stable and finally they can complete the thesis. This study aims to determine the effect of thought stopping. Thought Stopping was done by training the client to cut off disturbing thoughts by saying stop and change to positive thinking. The design used is a pre-test post-test control group design. The research instrument used an anxiety scale for thesis preparation. The results of the Mann Whitney U test in the post-test and follow-up of the experimental group and control group found each z-value of -2.619, p-value of 0.009 (p<0.05). The results showed that experimental group experienced a decrease in anxiety compared to the control group. The Wilcoxon Rank Test showed that there was a difference anxiety before and after thought stopping, with a z-value of -2.023, and a p-value of 0.043 (p<0.05).